Do trust and renewable energy use enhance perceived climate change efficacy in Europe? - Peter Dirksmeier; Leonie Tuitjer (Environment, Development and Sustainability, 2022)
In the European Union, mitigation policies in the energy sector are one of the most important fields of political intervention for reducing emissions to achieve sustainability. Using renewable energy is moreover a central arena for perceived personal and political climate change efficacy, which describes an individual's perceived ability to positively contribute to the fight against climate change and their belief in the effectiveness of government and society to tackle climate change collectively. In this paper, we distinguish between perceived personal and political efficacy beliefs. We use multilevel regression to investigate the relationship between these two dependent variables and trust in national governments as well as renewable energy use in 20 European countries for the first time. Our analysis first finds that socio-demographic predictors for perceived personal and political climate change efficacy operate almost diametrically. Second, we find that trust in governments is a much stronger predictor for perceived political efficacy. Third, we find that renewable energy use is a significant and positive predictor for perceived personal efficacy but correlates negatively with political efficacy. Finally, we find some cross-national variation in our European sample for both dimensions of efficacy beliefs. Understanding what shapes personal and political efficacy is salient to enhance public acceptance for sustainable energy transitions.
Keywords: 330; Perceived personal climate change efficacy; Perceived political climate change efficacy; Mitigation; Europe; Trust; Renewable energy